Numerical Investigation of an Innovative Windbreak Design with Jet Flow Generated by an Air Curtain for Half-pipe Skiing - K. Liu; F. Liu; Q. Liu (Journal of Applied Fluid Mechanics, 2024)
The sport of half-pipe skiing, characterized by its dynamic maneuvers and high-speed descents, often faces challenges posed by unpredictable wind conditions.  To address this, an advanced wind-blocking system incorporating an air curtain capable of generating a jet flow is proposed. This pioneering design offers a dual advantage: the system can significantly reduce the windbreak size in the vertical dimension while maintaining a satisfactory wind-blocking effect. A comprehensive study is conducted to analyze the effects of the height of the windbreak and the jet emission angle from the air curtain. When the jet speed is 40 m/s, a 50° emission angle and a 2 m height of the windbreak result in an optimal wind-blocking effect. Furthermore, delving deeper to understand the underpinnings of this phenomenon, we discovered that a counterrotating vortex pair, which forms in the presence of this jet under crossflow conditions, plays a pivotal role in augmenting the wind-blocking capabilities of the system.